2012
DOI: 10.1111/clr.12089
|View full text |Cite
|
Sign up to set email alerts
|

Microscopical and microbiologic characterization of customized titanium abutments after different cleaning procedures

Abstract: This study confirmed that both plasma and ultrasonic treatments can be beneficially adopted for abutment cleaning process after laboratory technical stages, to supposedly favor soft tissue healing and implant-prosthetic connection stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 26 publications
4
64
0
2
Order By: Relevance
“…Two recent studies demonstrated that Argon plasma has a double effect on titanium abutments: pollutions removal and increase of cell adhesion (9,10). Treatment with Argon plasma has been shown to enhance osteoblast adhesion, early bone formation and osseointegration of titanium implants (26-28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies demonstrated that Argon plasma has a double effect on titanium abutments: pollutions removal and increase of cell adhesion (9,10). Treatment with Argon plasma has been shown to enhance osteoblast adhesion, early bone formation and osseointegration of titanium implants (26-28).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma cleaning, applied before ultraviolet light treatment, enhanced surface energetics but did not affect cell attachment and spreading. In more recent “in vitro” studies, plasma of Argon cleaning treatment was demonstrated to have a double effect on titanium abutments: removal of pollutions following customization and increase of cell adhesion (9,10). …”
Section: Introductionmentioning
confidence: 99%
“…Presence of microbiologic contamination has been observed on prosthetic components after laboratory procedures and handling by office personnel 7 . Such debris could directly or indirectly trigger the inflammatory response of peri‐implant tissues 8 .…”
mentioning
confidence: 99%
“…Such debris could directly or indirectly trigger the inflammatory response of peri‐implant tissues 8 . Different cleaning methods have been used to disinfect the abutments before insertion, including the use of autoclaves, ovens, chemical agents (e.g., ethylene oxide), and plasma treatment 7 , 9 , 10 …”
mentioning
confidence: 99%
“…Neben der Politur spielt die Reinigung eine wesentliche Rolle. Eine aktuelle Studie[8] besagt, dass durch das reine Abdampfen des Abutments Bearbeitungspartikel auf der Oberfläche verbleiben können (z. B. Polierreste).…”
unclassified